Fetuin-A levels and free leptin index are reduced in patients with chronic lymphocytic leukemia: a hospital-based case-control study. - Dalamaga, Maria; Polyzos, Stergios A; Karmaniolas, Konstantinos; Chamberland, John; Lekka, Antigoni; Triantafilli, Maria; Migdalis, Ilias; Papadavid, Evangelia; Mantzoros, Christos S (Leuk Lymphoma, 2016)
There are limited data on fetuin-A, soluble leptin receptor (sOB-R) and free leptin index (FLI) in patients with chronic lymphocytic leukemia (CLL). The aim of this study was to compare circulating fetuin-A, sOB-R levels and FLI between 95 patients with CLL and 95 matched controls, as well as among different stages of CLL. Circulating fetuin-A was significantly lower in cases than controls (241.9 ± 99.2 vs. 288.8 ± 127.7 μg/mL; p = 0.005). Although circulating sOB-R levels were similar between groups, FLI was lower in cases than controls (0.45 ± 0.42 vs. 0.67 ± 0.57; p = 0.003). Furthermore, lower fetuin-A or FLI, but not sOB-R, were independently associated with CLL (p < 0.05), particularly among overweight/obese individuals. Fetuin-A, s-OB-R and FLI were similar between different stages of CLL severity, or between symptomatic and asymptomatic disease. In conclusion, circulating fetuin-A and FLI, but not sOB-R, were lower in patients with CLL than controls, a finding warranting further investigation.
Keywords: Aged; alpha-2-HS-Glycoprotein; Biomarkers; Case-Control Studies; Female; Humans; Leptin; Leukemia, Lymphocytic, Chronic, B-Cell; Male; Middle Aged; Neoplasm Staging; Odds Ratio; Prognosis; Risk Factors